Relationship Between Parental Knowledge And The Prevention Behaviour Of School – Aged Children Against The Missue Of Narcotics Specifically Aibon Inhalant - Henry, Chessy Miller; Hardayati, Yunita Astriani; Suprapti, Fitriana (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2024)
Addictive substances are materials that can cause addiction or dependence and can harm one's health status. In June 2022, there was recorded glue sniffing activity among school-aged children in Mimika, Central Papua, which can endanger their future and well-being. This research aims to analyze the relationship between parental knowledge and prevention behaviour regarding the misuse of Aibon glue, a type of addictive substance, among school-aged children. Data collection was conducted using an online form from March to April 2023 in the Inauga sub-district of Mimika. The research employed a quantitative approach with a descriptive correlational research design using a cross-sectional approach. The sample consisted of 111 respondents, selected using purposive sampling technique. The research instruments used were knowledge and prevention behaviour questionnaires. The results of the study showed that the majority of respondents were female (73.9%), in the early adulthood age category (26-35 years) (92.8%), and had a Diploma degree or equivalent education (48.6%). The majority of respondents had good knowledge (94.6%) and prevention behaviour (82.9%). Bivariate analysis using the chi-square test in SPSS version 25 indicated a significant relationship between parental knowledge and prevention behaviour regarding the misuse of Aibon glue, with a p-value of 0.000 (p < 0.05). The conclusion of this study is that better parental knowledge is associated with better prevention behaviour. This research is expected to serve as a reference for parents to understand that knowledge needs to be accompanied by preventive behaviour. With adequate knowledge, parents can implement prevention behaviour for their children.